P49 Birthweight, lifetime obesity and physical functioning in mid-adulthood: a nationwide birth cohort study. (3rd September 2019) - Rogers, NT; Power, C; Pereira, SP
Abstract : Background: Physical functioning from mid-adulthood is important for maintaining independence and is linked to better health outcomes. Evidence is scant on long-term implications of childhood obesity and body mass index (BMI) gains over the life-course for poor physical functioning (PF) in midlife. Studies that link obesity to poor PF have typically been cross-sectional, limited to two time-points or relied on retrospectively recalled height and weight. We aimed to establish associations between PF at age 50y and i) birthweight and BMI across the life-course; ii) BMI gains at specific life-stages and iii) age of obesity onset. Methods: The 1958 birth cohort includes all born in one week, in March 1958, across Britain. BMI (kg/m2) was calculated (N=4, 173 (males); 4, 501 (females)) using height and weight measured at school (7, 11, 16y), in participant's homes (33, 45y) or self-reported (23, 50y). PF at 50y was assessed via postal questionnaire using the validated PF subscale of the Short-form 36 (SF-36) survey. The lowest sex-specific 10th centile were defined as poor PF. Missing data was imputed via multiple imputation. Associations were examined using logistic regression, adjusting for social class, education and health behaviours. Results: Birthweight was not associated with PF. At each adult age, odds of poor PF were highest for obese (vs normal) e.g. for 23y obesity the ORadjusted for poor PF was 2.28(1.34, 3.91) and 2.67(1.72, 4.14) in males and females respectively. BMI gains from adolescence were related to poor PF, e.g. for females, ORadjusted per SD in BMI gain between 16–23y was 1.28(1.13, 1.46); for BMI gains 45–50y it was 1.36(1.11, 1.65). Mean BMI at 50y increased with earlier onset of obesity; e.g. in males, from 31.4 kg/m 2 for mid-adult onset to 35.1 kg/m 2 for child onset. Longer duration of obesity was associated with poor PF (p-trend<0.001), e.g. in males, for childhood obesity onset (vs. never obese) ORadjusted was 2.32(1.26, 4.29); for mid-adulthood obesity onset it was 1.50(1.16, 1.96); associations were abolished with further adjustment for 50y BMI. Conclusion: Study strengths include the large nationwide cohort followed from birth and prospective measures of BMI and PF, albeit BMI at some ages was self-reported. Obesity, BMI gains and earlier obesity onset were associated with poor PF in mid-adulthood. Findings relating to duration of obesity are important given the increasing prevalence of childhood obesity, which tends to track into adulthood. Our study highlights the importance of preventing and delaying obesity onset to mitigate the risk of poor PF in mid-adulthood.